What saccadic eye movements tell us about TMS-induced neuromodulation of the DLPFC and mood changes: a pilot study in bipolar disorders - Beynel, Lysianne; Chauvin, Alan; Guyader, Nathalie; Harquel, Sylvain; Szekely, David; Bougerol, Thierry; Marendaz, Christian (Frontiers in Integrative Neuroscience, 2014)
The study assumed that the antisaccade (AS) task is a relevant psychophysical tool to assess (i) short-term neuromodulation of the dorsolateral prefrontal cortex (DLPFC) induced by intermittent theta burst stimulation (iTBS) and (ii) mood change occurring during the course of the treatment. Saccadic inhibition is known to strongly involve the DLPFC, whose neuromodulation with iTBS requires less stimulation time and lower stimulation intensity, as well as results in longer aftereffects than the conventional repetitive transcranial magnetic stimulation (rTMS). Active or sham iTBS was applied every day for three weeks over the left DLPFC of 12 drug-resistant bipolar depressed patients. To assess the iTBS-induced short-term neuromodulation, the saccadic task was performed just before (S1) and just after (S2) the iTBS session, the first day of each week. Mood was evaluated through MADRS scores and the difference in scores between the beginning and the end of treatment was correlated with AS performance change between these two periods. As expected, only patients from the active group improved their performance from S1 to S2 and mood improvement was significantly correlated with AS performance improvement. In addition, the AS task also discriminated depressive bipolar patients from healthy control subjects. Therefore, the AS task could be a relevant and useful tool for clinicians to assess if the TMS-induced short-term neuromodulation of the DLPFC occurs as well as a ‘trait vs. state’ objective marker of depressive mood disorder.